Investigation of Thermomorphogenesis-Related Genes for a Multi-Silique Trait in Brassica napus by Comparative Transcriptome Analysis - Chai, Liang; Zhang, Jinfang; Li, Haojie; Cui, Cheng; Jiang, Jun; Zheng, Benchuan; Wu, Lintao; Jiang, Liangcai (Frontiers in Genetics, 2021)
In higher plants, the structure of a flower is precisely controlled by a series of genes. An aberrance flower results in abnormal fruit morphology. Previously, we reported multi-silique rapeseed (Brassica napus) line zws-ms. We identified two associated regions and investigated differentially expressed genes (DEGs); thus, some candidate genes underlying the multi-silique phenotype in warm area Xindu were selected. However, this phenotype was switched off by lower temperature, and the responsive genes, known as thermomorphogenesis-related genes, remained elusive. So, based on that, in this study, we further investigated the transcriptome data from buds of zws-ms and its near-isogenic line zws-217 grown in colder area Ma’erkang, where both lines showed normal siliques only, and the DEGs between them analyzed. We compared the 129 DEGs from Xindu to the 117 ones from Ma’erkang and found that 33 of them represented the same or similar expression trends, whereas the other 96 DEGs showed different expression trends, which were defined as environment-specific. Furthermore, we combined this with the gene annotations and ortholog information and then selected BnaA09g45320D (chaperonin gene CPN10-homologous) and BnaC08g41780D [Seryl-tRNA synthetase gene OVULE ABORTION 7 (OVA7)-homologous] the possible thermomorphogenesis-related genes, which probably switched off the multi-silique under lower temperature. This study paves a way to a new perspective into flower/fruit development in Brassica plants.